Targeting presynaptic norepinephrine transporter in brown adipose tissue: A novel imaging approach and potential treatment for diabetes and obesity - Mirbolooki, M. Reza; Constantinescu, Cristian C.; Pan, Min-Liang; Mukherjee, Jogeshwar (Synapse (New York, N.Y.), 2013)
Brown adipose tissue (BAT) plays a significant role in metabolism. In this study, we report the use of atomoxetine (a clinically applicable norepinephrine reuptake inhibitor) for 18F‐FDG PET imaging of BAT and its effects on heat production and blood glucose concentration. Fasted‐male Sprague‐Dawley rats were administered with intravenous 18F‐FDG. The same rats were treated with atomoxetine (0.1 mg/kg, i.v.) 30 min before 18F‐FDG administration. To confirm the β‐adrenergic effects, propranolol (β‐adrenergic inhibitor) 5 mg/kg was given intraperitoneally 30 min prior to atomoxetine administration. The effect of atomoxetine on BAT metabolism was assessed in fasted and non‐fasted rats and on BAT temperature and blood glucose in fasted rats. In 18F‐FDG PET/CT images, interscapular BAT (IBAT) and other areas of BAT were clearly visualized. When rats were fasted, atomoxetine (0.1 mg/kg) increased the 18F‐FDG uptake of IBAT by factor of 24 within 30 min. Propranolol reduced the average 18F‐FDG uptake of IBAT significantly. Autoradiography of IBAT and white adipose tissue confirmed the data obtained by PET. When rats were not fasted, atomoxetine‐induced increase of 18F‐FDG uptake in IBAT was delayed and occurred in 120 min. For comparison, direct stimulation of β3‐adrenreceptors in non‐fasted rats with CL‐316, 243 occurred within 30 min. Atomoxetine‐induced IBAT activation was associated with higher IBAT temperature and lower blood glucose. This was mediated by inhibition of norepinephrine reuptake transporters in IBAT leading to increased norepinephrine concentration in the synapse. Increased synaptic norepinephrine activates β3‐adrenreceptors resulting in BAT hypermetabolism that is visible and quantifiable by 18F‐FDG PET/CT. Synapse, 2013. © 2012 Wiley Periodicals, Inc.